PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF CANVA DENGAN PENDEKATAN DEEP LEARNING MATERI KETERAMPILAN MENULIS PANTUN PESERTA DIDIK SEKOLAH DASAR - Siswanti; Sujinah; Ali Nuke Affandy (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Interest and ability in writing pantun among fifth-grade students were still relatively low. Students experienced difficulties in understanding the structure of pantun, selecting appropriate diction, and expressing ideas creatively in written form. This study aimed to develop an interactive learning media based on Canva with a deep learning approach for teaching pantun writing skills and to examine its practicality and effectiveness for fifth-grade students at SDN Tanah Kalikedinding II Surabaya. The research employed a Research and Development (R&D) method using the 4D model, which consisted of define, design, develop, and disseminate stages. The development subjects included material and language experts as well as a media expert who served as validators, while the trial subjects involved the fifth-grade teacher and students. Both quantitative and qualitative data were collected through questionnaires, interviews, and learning achievement tests. The research instruments consisted of expert validation sheets, teacher and student response questionnaires, and formative and summative assessment tests. Data were analyzed descriptively to determine the validity, practicality, and effectiveness of the developed media. The results indicated that the media was highly valid, with a score of 97% from material and language experts and 95% from the media expert. The practicality was categorized as very high based on teacher responses (96.80%) and student responses (99.07%). The effectiveness was reflected in the average formative score of 86 and summative score of 91, with an overall average of 89 (high category). The Canva-based deep learning media effectively improved students’ understanding and pantun writing skills.